2014
DOI: 10.1590/s0100-06832014000500001
|View full text |Cite
|
Sign up to set email alerts
|

Public-domain software for root image analysis

Abstract: SUMMARYIn the search for high efficiency in root studies, computational systems have been developed to analyze digital images. ImageJ and Safira are public-domain systems that may be used for image analysis of washed roots. However, differences in root properties measured using ImageJ and Safira are supposed. This study compared values of root length and surface area obtained with public-domain systems with values obtained by a reference method. Root samples were collected in a banana plantation in an area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
(38 reference statements)
0
10
1
6
Order By: Relevance
“…The coefficients of determination values were quite different from those obtained from Safira. However, the determination of coefficient R² = 0.733 is better than the low values of determination coefficient (R² = 0.514 and 0.453), in root length measures of banana (Costa et al, 2014). This indicates that our method explains root length better than Safira.…”
Section: Test With Soybean Rootsmentioning
confidence: 69%
See 3 more Smart Citations
“…The coefficients of determination values were quite different from those obtained from Safira. However, the determination of coefficient R² = 0.733 is better than the low values of determination coefficient (R² = 0.514 and 0.453), in root length measures of banana (Costa et al, 2014). This indicates that our method explains root length better than Safira.…”
Section: Test With Soybean Rootsmentioning
confidence: 69%
“…In 0-20 cm soil layers, where these values are strong, we can concluded that reference method shows an increase in root length compared to the tested software (Our Method and Safira). Overall, the software developed to facilitate root studies using image processing are positively correlated with the conventional method (Costa et al, 2014). In studies using image processing, which compared WinRHIZO™ with the Tennant method, the morphological root parameters of winter wheat generated by these two methods were positively correlated, but significantly different (Wang and Zhang, 2009).…”
Section: Test With Soybean Rootsmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge for root studies is to improve techniques and methods for root sampling and root system architecture quantification7. A rich number of sampling and phenotyping methods for crop roots in the field have been proposed, including soil profiles8, monoliths9, nail plates, probes10, rhizotron8, trenching11, shovelomics12 and digitalization and visualization of roots in field1314. These methods supply a number of parameters, e.g.…”
mentioning
confidence: 99%